2002
DOI: 10.1080/09553000210132306
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced apoptosis in the scid mouse spleen after low dose-rate irradiation

Abstract: These data suggest that DNA-PK activity might play a major role in the radioadaptive response following pre-irradiation at a low dose-rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Further, although apoptosis was not investigated in this study, it is possible that BM cells of SCID/J mice are capable of removing some of the damaged cells by means of apoptosis. The non-harmful effects of low doses and low dose-rates of low LET radiation via apoptosis have previously been reported in the spleen of SCID mice [54,55]. In those studies, a role for p53 proteins in apoptosis induced by low dose or low dose-rate of low LET radiation has been suggested.…”
Section: Resultsmentioning
confidence: 94%
“…Further, although apoptosis was not investigated in this study, it is possible that BM cells of SCID/J mice are capable of removing some of the damaged cells by means of apoptosis. The non-harmful effects of low doses and low dose-rates of low LET radiation via apoptosis have previously been reported in the spleen of SCID mice [54,55]. In those studies, a role for p53 proteins in apoptosis induced by low dose or low dose-rate of low LET radiation has been suggested.…”
Section: Resultsmentioning
confidence: 94%
“…In this sense, it has been reported that DNA-dependent proteinkinases activity might play an important role in the radioadaptive response. This mechanism might be due to the suppression of p53-mediated apoptosis (Takahashi et al , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Because time is required for these processes, an interval between low‐dose irradiation and subsequent high‐dose irradiation is necessary to achieve radioresistance. Many factors contribute to the adaptive response in each process, as summarized in Table 3 40,43,50–65 …”
Section: Adaptive Response To Oxidative Stress and Agingmentioning
confidence: 99%